1982
DOI: 10.1021/ja00371a045
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a new surface derivatizing reagent to promote the adhesion of polypyrrole films to N-type silicon photoanodes: N-(3-(trimethoxysilyl)propyl)pyrrole

Abstract: J . Am. Chem. SOC. natural tylosin (vide infra). To complete the synthesis, 6 was selectively reduced (4.0 equiv of Dibal, CH2C12, -78 "C, reduction of dienone and y-lactone) and oxidized (1.3 equiv of DDQ, benzene, 25 "C) to produce 0-mycinosyltylonolide (1) in 76% overall yield. Synthetic 1 was identical in all respects with an authentic sample obtained by degradation of tylosin as described below.Mild acid hydrolysis of tylosin (7) (Scheme I) (dilute HC1, THF, 25 OC or AcOH-THF-H20, 25 "C) detaches only myc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(84 citation statements)
references
References 3 publications
2
82
0
Order By: Relevance
“…The immobilization of electroactive p-conjugated systems on gold surfaces by formation of self-assembled monolayers (SAMs) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] has recently become a focus of high interest motivated by their potential applications in the field of functionalized surfaces, [1] sensors, [2] molecular electronics, [3] or molecular heterojunctions for photovoltaic conversion. [4] On the other hand, several groups have reported the use of surface-immobilized electropolymerizable systems as starting point for the deposition of electrogenerated electroactive conducting polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immobilization of electroactive p-conjugated systems on gold surfaces by formation of self-assembled monolayers (SAMs) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] has recently become a focus of high interest motivated by their potential applications in the field of functionalized surfaces, [1] sensors, [2] molecular electronics, [3] or molecular heterojunctions for photovoltaic conversion. [4] On the other hand, several groups have reported the use of surface-immobilized electropolymerizable systems as starting point for the deposition of electrogenerated electroactive conducting polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[4] On the other hand, several groups have reported the use of surface-immobilized electropolymerizable systems as starting point for the deposition of electrogenerated electroactive conducting polymers. [5][6][7][8][9][10][11][12] Wrighton and coworkers used pyrrole attached on silicon by a silane group to promote the adhesion of subsequently electropolymerized poly(pyrrole). [6] More recently, this method has been extended to other systems such as pyrrole-containing dendrimers, [7] aniline, [8] carbazole, [9] thiophene, and oligothiophenes derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…The method used in this study was essentially that reported by Simon et al [9]. Briefly, after drying at 80"C, the etched electrodes were placed inside dry flat-bottomed glass tubes containing small magnetic followers.…”
Section: Surface Modification Of the Silicon Electrodesmentioning
confidence: 99%
“…8 Up to now, several studies reported on using pyrrole-functionalized organosilanes to increase the adhesion of the polymers to the substrate. For example, 3-(pyrrol-1-yl) propyl trimethoxylsilane was successfully used by Simon et al 9 and Wu et al 10 for adhering PPy on silicon substrate; Cossement obtained dense and adhesive PPy films by grafting polypyrrole on the 6-(pyrrol-1-yl)-n-hexyl trichlorosilane modified ITO electrode; 11 Guiseppi-Elie et al 5 and Faverolle et al 12 used other pyrrole-substituted organosilane monolayers for grafting PPy on SiO 2 substrates; Shustak et al 13 used n-alkanoic acid monolayer to promote the adhesion of polypyrrole on stainless steel. However, all above mentioned adhesion promoters are 1-substituted pyrrole organosilane.…”
Section: Introductionmentioning
confidence: 99%